Invitations to mutual learning: Reflections on co-researching a social prescribing model of care during the COVID 19 pandemic - Salter, Leah (Murmurations: Journal of Transformative Systemic Practice, 2021)
This paper offers some reflections on the creative and ethical approaches to participant inclusion in a research project which is currently taking place in the time of the COVID 19 pandemic. The project is based in the county of Bridgend, South Wales, UK. An account of one of the storytelling projects this paper refers to was published in the last edition of Murmurations (Salter, 2020). These reflections focus on the early invitation to intervention phase of the research that might traditionally be thought of as the recruitment phase, followed by interview-conversations with participants. The language of recruitment and interviewing suggests or assumes that the researcher goes in blindly and coldly with some kind of promotional campaign to find people they previously did not know and then co-opt them into a study where they are the participant or the object of study. In relational, practice-based research such as the one featured here, this does not reflect the ethics of systemic values nor community-based practice. This paper describes an alternative model to think about co-inquiry as an invitation to mutual learning. The method and the ethics of inquiry are spotlighted in this paper, within an overview of the context to inquiry - that of researching a social prescribing model of care. The paper also offers a brief reflection on learning in this early stage with contributions from co-researchers.